Employment–Growth Nexus in Uganda: Analysis with Error Correction Modelling - TURYAREEBA, DICKSON; Ainomugisha, Peter; Mbabazize, Robert; Ssebbaale, Edward Mukasa; Mulema, Sabiiti; Wemesa, Richard; Wagima, Christopher; Bakaki, Ivan (Archives of Business Research, 2020)
Purpose–The purpose of the study is to examine the link between economic growth and employment growth in Uganda. Methodology–The study adopts the causal relationship research design. Times series quarterly data for the period 2001-2018 are used to study the underlying relationship. Descriptive statistics are generated to describe data behavior and econometric models are developed to estimate short run and long run national employment intensities of economic growth. A single-equation based Engel-Granger two-step Error Correction Mechanism is used to estimate the coefficients of the empirical model. Findings– Estimates reveal that whereas employment growth and economic growth show no causal link in the short run, the two variables show a positive and statistically significant causal link in the long run. The long run employment intensity of economic growth is however less than unity, suggesting that Uganda’s long run economic growth is not employment intensive. Originality/value-The study results provide empirical evidence on the role of economic growth on employment creation in Uganda while unveiling evidence of jobless growth. Practical implications- Results suggest that adopting pro-poor and growth inclusive interventions may be prudent for job creation for the Ugandan labour force.